Complications of Asian Double Eyelid Surgery: Prevention and Management - Young, Stephanie Ming; Kim, Yoon-Duck (Facial Plastic Surgery, 2020)
Double eyelid surgery remains one of the most popular aesthetic surgeries, especially among East Asian populations. Complications related to double eyelid surgery can be divided into various categories: (1) patient dissatisfaction, (2) problems with the eyelid crease, (3) problems with the eyelid height, (4) suture-related complications, and (5) complications related to eyelid surgery in general. As with all eyelid surgeries, it is important to understand and appreciate the normal and abnormal function and anatomy of the Asian eyelid to reduce the risk of complications. It is also important to recognize the various complications and their underlying causes so that the surgeon can confidently revise the surgery to achieve optimal outcomes.
Keywords: double eyelid surgery; cosmetic surgery; complications; Asian blepharoplasty; suture blepharoplasty